Psychometric Validation of the Greek Version of the Scale "Temper Loss" of the Questionnaire "Multidimensional Assessment Profile of Disruptive Behavior (MAP-DB)" - Maria Micha; Gerasimos Makris; Maria Michou; Christina Kanaka-Gantenbein; Lauren Wakschlag; Panagiota Pervanidou (MDPI AG, 2022)
It has become increasingly evident that vulnerability to psychopathology is identifiable early in life. A body of evidence suggests that the recognition and prevention of a spectrum of typical/atypical behaviors in preschoolers can lead to earlier diagnosis and treatment. The Multidimensional Assessment Profile of Disruptive Behavior (MAP-DB) is a parent-completed instrument that has been developed recently to differentiate normative misbehaviors in early childhood from markers of clinical risk. The aim of the present study was to validate the "Temper Loss" Subscale in the Greek language and to assess its psychometric properties in healthy children. An on-print parent-report survey was conducted among Greek children, aged between 3 and 5.5 years. The survey included the MAP-DB and the Child Behavior Checklist (CBCL). A total of 400 respondents participated in the study. The analysis suggested that the Greek version of the MAP-DB's "Temper Loss" scale has good psychometric properties. The results of the Exploratory Factor Analysis (EFA) of the 22 items were able to explain 64.4% of the total variance. Internal consistency for the one subscale was satisfactory, with Cronbach's alpha at 0.970. This scale can be used by researchers and practitioners for the evaluation of dimensional phenotypes in early childhood.